Marine soundscape and its temporal acoustic characterisation in the Gulf of Oristano, Sardinia (Western Mediterranean Sea) - CORRIAS, VALENTINA; DE LUCIA, GIUSEPPE ANDREA; FILICIOTTO, FRANCESCO (Mediterranean Marine Science, 2023)
The soundscape of the marine environment is a combination of geophony, biophony and anthropophony. Here, the soundscape of the Gulf of Oristano, a shallow inlet on the western coast of Sardinia including a special conservation area (Habitat Directive) and a national marine protected area, was investigated. Data collection was performed during July 2019, November 2019 and May 2020 using underwater acoustic equipment. The goal of this study was to characterise the ambient sound levels (Sound Pressure Level dB re 1 μPa) and describe the main soundscape components. The soundscape exhibited significant circadian and seasonal variations: the lowest and highest median SPL values were observed in the Spring (120–140 dB re 1 μPa; post-COVID-19 pandemic lockdown) and the Summer (128–150 dB re 1 μPa) respectively. Biophony was identified and characterised as dolphins’ ‘clicks’ and crustaceans’ ‘snapping’. Shrimp activity was dominant in the summer, while dolphin passages were observed across all sampling periods, accounting for 46.4% of the total recordings. Anthropophony, namely vessel passages, was predominant in the summer during the day-time and represented up to 42% of the acoustic space in the low-frequency band. Geophony increased low-frequency noise, and represented a highly variable component of the local soundscape. The marine soundscape is a valuabletool for defining integrated management plans for marine ecosystems, allowing the assessment of habitat quality, characterisation of sound sources and evaluation of the impact of anthropogenic activities.